The Neglected Genes of ALS: Cytoskeletal Dynamics Impact Synaptic Degeneration in ALS - Castellanos-Montiel, María José; Chaineau, Mathilde; Durcan, Thomas M. (Frontiers in Cellular Neuroscience, 2020)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease that selectively affects motor neurons (MNs) of the cortex, brain stem and spinal cord. Several genes have been linked to both familial (fALS) and sporadic (sALS) cases of ALS. Among all the ALS-related genes, a group of genes known to directly affect cytoskeletal dynamics (ALS2, DCTN1, PFN1, KIF5A, NF-L, NF-H, PRPH, SPAST and TUBA4A) is of high importance for MN health and survival, considering that MNs are large polarized cells with axons that can reach up to one meter in length. In particular, cytoskeletal dynamics facilitate the transport of organelles and molecules across the long axonal distances within the cell, playing a key role in synapse maintenance. The majority of ALS-related genes affecting cytoskeletal dynamics were identified within the past two decades, making it a new area to explore for ALS. The purpose of this review is to provide insights into ALS-associated cytoskeletal genes and outline how recent studies have pointed towards novel pathways that might be impacted in ALS. Further studies making use of the newest technologies such as CRIPSR/Cas9, human induced pluripotent stem cells (iPSCs) and axon sequencing, as well as the development of more transgenic animal models could potentially increase our understanding of the neglected ALS-related genes affecting cytoskeletal dynamics.